IMPLEMENTASI ASEAN PLAN OF ACTION TO COMBAT TRANSNATIONAL CRIMES (STUDI KASUS HUMAN TRAFFICKING DI THAILAND PADA TAHUN 2006-2010) - Ani Khoirunnisa (Universitas 17 Agustus 1945 Jakarta, 2018)
AbstractThe concept of human security is related to components that can not be replaced if the components are lost. Aside that the assessment of human security (especially for human trafficking cases) tends to be subjective so that parameters are difficult to determine universally. Citizens as an object must be protected by every states. But each states has their own interest on profits that will be obtained as foreign exchange. Therefore, this paper will describe the problem of human trafficking in Thailand, which is difficult to deal with by states even though they have joint regulations. It cause by the difference of national interests. Although the community have the principle of non-intervention.Keywords: human security, human trafficking, national interests.